2011
DOI: 10.1590/s0100-736x2011000900005
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the efficacy of hydrated sodium aluminosilicate in the prevention of aflatoxin-induced hepatic cancer in rainbow trout

Abstract: The use of aluminum silicates for decontaminating animal feed containing aflatoxins has yielded encouraging results in chicken and turkey poults. In contrast, very few studies have tested these substances in aquaculture. In this work, we investigated the efficacy of a trout diet containing 0.5% hydrated sodium aluminosilicate (HSAS) in protecting against contamination with aflatoxin B1. Trout were reared on these diets for one year and the experimental groups were examined monthly for hepatic presumptive prene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
0
9
0
3
Order By: Relevance
“…The following test products were used: Novasil Plus (HSCAS, Ca-montmorillonite, 62.4-73.5% SiO 2 , 14.8-18.2% Al 2 O 3 , 3.2-4.8% CaO, 4.0-4.5% MgO, 5.4-6.5% Fe 2 O 3 , 0.5-0.9% K 2 O, 0.1-0.3% Na 2 O, 0.01-0.03% MnO), Zeolex Extra (chemically activated organoaluminosilicate, 57-64% SiO 2 , 10-17% Al 2 O 3 , 3.3-4.9% CaO, 0.3-1.8% MgO, 0.6-1.4% Fe 2 O 3 , 1.8-2.8% K 2 O, 1.6-2.9% Na 2 O), Mycofix Select (diatomaceous earth 30%, kaolinite 50%, phytophytic substances 10%, herbal extracts 10%), and Fixat (bentonite-montmorillonite, 50-65% SiO 2 , 15-25% Al 2 O 3 , 3-6% CaO, 3-6% MgO, 3-6% una reducción notable del consumo de alimento, disminución de crecimiento, supresión del sistema inmunológico y lesiones hepáticas en truchas arcoiris (Arana et al 2011), carpas (Mohapatra et al 2011), tilapias (Shehata et al 2009), bagres (Dӧll et al 2010) y camarones (Boonyaratpalin et al 2001, Soonngam y Hutacharoen 2007, Gopinath y Raj 2009, TapiaSalazar et al 2012) alimentados con dietas contaminadas con aflatoxinas. Existen varios productos de desintoxicación comerciales para inactivar las micotoxinas en los alimentos para animales y su efecto desintoxicante consiste en la adsorción física, unión y secuestro de sustancias tóxicas (Kolossova et al 2009), que después son eliminadas junto con el desintoxicante.…”
Section: Aluminosilicate-based Productsunclassified
See 3 more Smart Citations
“…The following test products were used: Novasil Plus (HSCAS, Ca-montmorillonite, 62.4-73.5% SiO 2 , 14.8-18.2% Al 2 O 3 , 3.2-4.8% CaO, 4.0-4.5% MgO, 5.4-6.5% Fe 2 O 3 , 0.5-0.9% K 2 O, 0.1-0.3% Na 2 O, 0.01-0.03% MnO), Zeolex Extra (chemically activated organoaluminosilicate, 57-64% SiO 2 , 10-17% Al 2 O 3 , 3.3-4.9% CaO, 0.3-1.8% MgO, 0.6-1.4% Fe 2 O 3 , 1.8-2.8% K 2 O, 1.6-2.9% Na 2 O), Mycofix Select (diatomaceous earth 30%, kaolinite 50%, phytophytic substances 10%, herbal extracts 10%), and Fixat (bentonite-montmorillonite, 50-65% SiO 2 , 15-25% Al 2 O 3 , 3-6% CaO, 3-6% MgO, 3-6% una reducción notable del consumo de alimento, disminución de crecimiento, supresión del sistema inmunológico y lesiones hepáticas en truchas arcoiris (Arana et al 2011), carpas (Mohapatra et al 2011), tilapias (Shehata et al 2009), bagres (Dӧll et al 2010) y camarones (Boonyaratpalin et al 2001, Soonngam y Hutacharoen 2007, Gopinath y Raj 2009, TapiaSalazar et al 2012) alimentados con dietas contaminadas con aflatoxinas. Existen varios productos de desintoxicación comerciales para inactivar las micotoxinas en los alimentos para animales y su efecto desintoxicante consiste en la adsorción física, unión y secuestro de sustancias tóxicas (Kolossova et al 2009), que después son eliminadas junto con el desintoxicante.…”
Section: Aluminosilicate-based Productsunclassified
“…For rainbow trout, a few studies have shown that the supplementation of sodium aluminosilicates and bentonites to aflatoxin-contaminated diets reduces intestinal aflatoxin absorption (Ellis et al 2000, Hassan et al 2010; nevertheless, other studies have shown that the addition of aluminosilicates to aflatoxin-contaminated diets for catfish and rainbow trout did not ameliorate their toxic effect (Lopes et al 2009, Arana et al 2011. Suppadit et al (2006) and Soonngam and Hutacharoen (2007) observed that adding HSCAS or vermiculite to aflatoxin-contaminated diets lessened the negative effects triggered by the mycotoxin in Fixat presentaron una disminución en su consumo de alimento (alrededor de 10-12%) y tasa de crecimiento (alrededor de 4-17%); en contraste, los individuos alimentados con NCD + Novasil Plus mostraron un mayor consumo de alimento (alrededor de 6%) y tasa de crecimiento (alrededor de 8%).…”
Section: Effectiveness Of Aluminosilicates To Bind Aflatoxin In Shrimmentioning
confidence: 99%
See 2 more Smart Citations
“…The aflatoxins B 1 , B 2 , G 1 and G 2 produced by Aspergillus flavus and A. parasiticus are considered the most relevant group in Brazil due to their high incidence and the toxic effects they have on humans and animals (Arana et al 2011;Cardoso et al 2011;Hoeltz et al 2012). When ingested by an animal, AFB 1 is biotransformed in the liver and excreted in the milk as AFM 1 (Hussein and Brasel 2001).…”
Section: Introductionmentioning
confidence: 99%